2005
DOI: 10.1103/physrevb.72.174111
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation through a random array of pinned dislocations: Velocity change and attenuation in a generalized Granato and Lücke theory

Abstract: A quantitative theory of the elastic wave damping and velocity change due to interaction with dislocations is presented. It provides a firm theoretical basis and a generalization of the Granato and Lücke model ͓J. Appl. Phys. 27, 583 ͑1956͔͒. This is done considering the interaction of transverse ͑T͒ and longitudinal ͑L͒ elastic waves with an ensemble of dislocation segments randomly placed and randomly oriented in an elastic solid. In order to characterize the coherent wave propagation using multiple scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…42,43 The dependence of T rand NN on the length L of the slab containing the inclusions is linear, a consequence of the linearity of our equation in the single scattering approximation, which causes the prediction on the transmission unreliable for large L. The limit of T rand NN for a large slab is less problematic: Including a small attenuation in the host medium that produces a small imaginary part in k N , and the limit L ! 1 becomes possible [namely e 2ik N L vanishes in Eq.…”
Section: The Case Of Randomly Distributed Inclusions In a Waveguidementioning
confidence: 99%
“…42,43 The dependence of T rand NN on the length L of the slab containing the inclusions is linear, a consequence of the linearity of our equation in the single scattering approximation, which causes the prediction on the transmission unreliable for large L. The limit of T rand NN for a large slab is less problematic: Including a small attenuation in the host medium that produces a small imaginary part in k N , and the limit L ! 1 becomes possible [namely e 2ik N L vanishes in Eq.…”
Section: The Case Of Randomly Distributed Inclusions In a Waveguidementioning
confidence: 99%
“…This estimation showed that the contribution of dislocation damping to attenuation is the most important effect for the cold working metal and that the phenomenological Granato–Lücke model can be employed [20]. A further development of the theory includes averaging of the dislocation orientation and Burgers vectors but gives similar results [21]. Practically the most important result is that the decrease in the dislocation loop length shifts the maximum of the ultrasonic attenuation to higher frequencies.…”
Section: Attenuation Of Ultrasound Pulsesmentioning
confidence: 89%
“…In the case where many of these dislocations are present, with probability p(L)dL of having a length between L and L + dL, Maurel et al 2 used multiple-scattering theory to compute an effective, complex index of refraction whose real part gives a renormalized velocity of propagation for both longitudinal and transverse waves, and whose imaginary part provides an attenuation, also for both longitudinal and transverse waves. This is done in the following way: An homogeneous, isotropic, elastic medium is described by u i ( x,t), with the displacement of a particle at time t from its equilibrium position x, whose time derivative v i ≡ ∂u i /∂t obeys, in the presence of many dislocation segments, the inhomogeneous wave equation…”
Section: Effective Elastic Constantsmentioning
confidence: 99%